2014
DOI: 10.1007/s12011-014-0211-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Serum Zinc Levels in Young Japanese Women by Provision of Food Information

Abstract: We investigated whether or not an intervention of providing food information improves serum Zn levels in ninety-two 18-20-year-old Japanese women. The mean serum Zn level of the participants was 73.09 ± 10.56 (mean ± SD) μg/dL, where 79 % of the participants had lower than the reference Zn level (80 μg/dL) proposed by the Japan Society for Biomedical Research on Trace Elements. Participants were divided into food information (INF) group, supplement (SPL) group, and control (C) group, and their serum Zn levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[23] In a previous study, the authors examined the impact of dietary information provision on improving low Zn levels in young women. [35] That study revealed that approximately 60% of the subjects were potentially Zn-de cient before the provision of dietary information. Therefore, the prevalence of Zn de ciency in Japan is a concern not only among the children and elderly, but also among other age groups, including young people.…”
Section: Discussionmentioning
confidence: 99%
“…[23] In a previous study, the authors examined the impact of dietary information provision on improving low Zn levels in young women. [35] That study revealed that approximately 60% of the subjects were potentially Zn-de cient before the provision of dietary information. Therefore, the prevalence of Zn de ciency in Japan is a concern not only among the children and elderly, but also among other age groups, including young people.…”
Section: Discussionmentioning
confidence: 99%